(untitled) (Journal of the College of Basic Education, 2022)
The research problem is summarized about the concept of egoistic orientation among postgraduate students in the use of the university library, and after defining the terms and objectives, the theory of personal benefit for humans was adopted in building the scale and interpreting the results. They go to the university library. The sample included different scientific and human departments. Several statistical methods were used, which are chi-square - Pearson correlation coefficient - t-test for one sample and two independent samples. The scale paragraphs distinguish it with high reliability and reliability. The study reached the following results, conclusions and hypotheses.